2018
DOI: 10.20960/nh.1628
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Presence Anemia and Malnutrition in Hospitalized Patients With Exclusive Enteral Nutrition

Abstract: anemia has an important relation with anthropometric markers that evaluate the depletion of lean mass; the BMI has a strong association with all the anthropometric parameters evaluated, as well as the albumin and capillary blood glucose, except with the values of hemoglobin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Anaemia has already been reported as having an important relationship with LSA through systemic inflammation in hospitalized patients. 28 LSA is a frequent feature of chronic kidney disease and depends on many factors, not only albuminuria and inflammation but also albumin homeostasis. Especially in patients with end‐stage renal disease, LSA is also the result of decreased synthesis and increased degradation of protein.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia has already been reported as having an important relationship with LSA through systemic inflammation in hospitalized patients. 28 LSA is a frequent feature of chronic kidney disease and depends on many factors, not only albuminuria and inflammation but also albumin homeostasis. Especially in patients with end‐stage renal disease, LSA is also the result of decreased synthesis and increased degradation of protein.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that anemia was associated with decreased risk of fasciotomy may be explained by that anemia could be interpreted as a proxy for poor general health (8,9) and aging (10), as such, also lower muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the extent of reduction in serum Alb and Hb levels between the initial and last NST interventions tended to be lower in the early NST intervention group than in the delayed NST intervention group. Although biochemical markers are usually not changed by EN and tend to be affected by the patients' disease status or other confounding factors [36], serum Alb is a relatively sensitive marker for assessing dietary intake and protein deficiency [34,37] and low serum Alb level is associated with anemia and low Hb levels in EN patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…Since EN alone cannot provide sufficient amount of nutrition to meet patients' metabolic or physical need in the long term [25,38], patients tend to be malnourished at the end of tube feeding, as evidenced by the energy deficit [25] and decrease in biochemical parameters such as Alb and Hb levels [38]. The higher energy supply and smaller reduction in Alb and Hb levels in the early NST group than in the delayed NST group indicated that early NST prevented tube feeding-induced nutrition deficit; this may be the reason why both groups had more patients with severe malnutrition at the end of the NST intervention than at the beginning.…”
Section: Discussionmentioning
confidence: 99%